Disparities in cervical cancer elimination time frames in the United States: a comparative modeling study - Burger, Emily; Jansen, Erik E L; Bondt, Daniël D. de; Killen, James; Spencer, Jennifer C; Regan, Mary Caroline; Smith, Megan A; Sy, Stephen; Canfell, Karen; de Kok, Inge M C M; Kim, Jane J; Hontelez, Jan (Journal of the National Cancer Institute, 2025)
Population-level estimates in time frames for reaching cervical cancer elimination (ie, <4 cases per 100000 women) in the United States may mask potential disparities in achieving elimination among subpopulations. We used 3 independent Cancer Intervention and Surveillance Modeling Network models to estimate differences in the time to cervical cancer elimination across 7 strata of correlated screening and human papillomavirus vaccination uptake, based on national survey data. Compared with the average population, elimination was achieved at least 22 years earlier for the high-uptake strata and at least 27 years later for the most extreme low-uptake strata. Accounting for correlated uptake impacted the population average time frame by no more than 1 year. Consequently, national average elimination time frames mask substantial disparities in reaching elimination among subpopulations. Addressing inequalities in cervical cancer control could shorten elimination time frames and would ensure more equitable elimination across populations. Furthermore, country-level elimination monitoring could be supplemented by monitoring progress in subpopulations.
Gesehen am 20.08.2025